2006
DOI: 10.1590/s1807-59322006000500017
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sex Hormones Influence the Response to Trauma and Sepsis – Potential Therapeutic Approaches

Abstract: Several clinical and experimental studies have demonstrated gender dimorphism in immune and organ responsiveness and in the susceptibility to and morbidity from shock, trauma, and sepsis. In this respect, cell-mediated immune responses have been shown to be depressed in males following trauma-hemorrhage, whereas they were aintained/enhanced in proestrus females. Furthermore, sex hormones have been shown to be responsible for this gender-specific immune response following adverse circulatory conditions. More sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0
18

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 76 publications
(112 reference statements)
1
67
0
18
Order By: Relevance
“…In rodents, E2 levels are lowest during estrus and metestrus, gradually increasing during diestrus, and reaching a peak at proestrus stage (63). It has been demonstrated that female hormones, E2 and prolactin, modulate immune responsiveness in adult mice and that the proestrus state of the estrus cycle is characterized by a more vigorous immune response compared with the diestrus state (64)(65)(66)(67). The observed restoration of organ function following trauma-hemorrhage after flutamide administration was also found to be estrogen-mediated, owing to increases in estrogen levels by increasing the conversion of testosterone to estrogen (68).…”
Section: Immune Alterations After Trauma-hemorrhage and The Role Of Ementioning
confidence: 99%
“…In rodents, E2 levels are lowest during estrus and metestrus, gradually increasing during diestrus, and reaching a peak at proestrus stage (63). It has been demonstrated that female hormones, E2 and prolactin, modulate immune responsiveness in adult mice and that the proestrus state of the estrus cycle is characterized by a more vigorous immune response compared with the diestrus state (64)(65)(66)(67). The observed restoration of organ function following trauma-hemorrhage after flutamide administration was also found to be estrogen-mediated, owing to increases in estrogen levels by increasing the conversion of testosterone to estrogen (68).…”
Section: Immune Alterations After Trauma-hemorrhage and The Role Of Ementioning
confidence: 99%
“…Изучение вопроса о связи пола с реакци ей иммунной системы на ишемию привело исследовате лей к заключению об угнетающем действии на иммун ную систему мужских стероидных гормонов и активирующего влияния женских половых гормонов или их соотношения [10][11][12][13]. Полученные результаты не связаны с влиянием исследуемых препаратов на гипоталамо гипофизарно надпочечниковую систему, т. к. при их введении неболь шое повышение кортикостерона по сравнению с группа ми контрольных реанимированных крыс наблюдалось лишь при использовании дерината.…”
Section: результаты и обсуждениеunclassified
“…Известны данные о половых раз личиях этой реакции у человека и животных, перенес ших терминальное состояние [8][9][10][11][12][13]. Учитывая извест ные в литературе факты о влиянии стероидных половых гормонов на постреанимационное восстановление ЦНС [14][15][16], а также на иммунный ответ организма, находя щегося в критическом состоянии [9,10], цель настояще го исследования заключалась в оценке воздействия пана вира и дерината, обладающих иммуностимулирующими свойствами, на постреанимационный процесс у живот ных разного пола.…”
unclassified
“…По данным экспериментальных ис-следований морфофункциональное состоя-ние иммунной системы у самок циклически изменяется в зависимости от фазы эстраль-ного цикла [2,5]. «Эстрогеновый статус» является одним из факторов, модулирую-щих выраженность иммунного ответа [2].…”
unclassified
“…«Эстрогеновый статус» является одним из факторов, модулирую-щих выраженность иммунного ответа [2]. По сравнению с другими фазами эстраль-ного цикла фаза проэструса, при которой наблюдается максимальный уровень эстра-диола в сыворотке крови (100-200 пг/мл у крыс), характеризуется наиболее выражен-ной реакцией иммунной системы на анти-генные воздействия [2,11].…”
unclassified